Introducing the Construct of the Jury into Family Violence Proceedings and Family Court Jurisprudence - Breger, Melissa L. (2006)
This Article draws upon both the theory of and research on procedural justice holding that litigants often focus on the appearance of fairness rather than on the actual outcome. Thus, when litigants are able to choose the modality of fact-finding, they may be more accepting of the legal process, even if the outcome is not favorable to them. Allowing the option of a jury, even if not exercised, may dramatically improve the perceptions of litigants and may affect the legitimacy and longevity of case outcomes